Performance of Elaeis Guineensis Leaves Compost in Filter Media for Stormwater Treament Through Column Study - Takaijudin, H. (Institute of Physics Publishing, 2016)
Compost based materials arv e widely used in filter media for improving soil capability and plant growth. The aim of this paper is to evaluate different types of compost materials used in engineered soil media through soil column investigation. Three (3) column, namely C1 (control), C2 and C3 had different types compost (10) which were, commercial compost namely PEATGRO, Compost A and Compost B were prepared with 60 medium sand and 30 of topsoil. The diluted stormwater runoff was flushed to the columns and it was run for six (6) hour experiment. The influent and effluent samples were collected and tested for Water Quality Index (WQI) parameters. The results deduced that C3 with Elaeis Guineensis leaves compost (Compost B) achieved 90.45 (Class II) better than control condition which accomplished 84 (Class II) based on WQI Classification. C3 with Compost A (African Mahogany Leaves Compost) obtained only 59.39 (Class III). C3 with the composition of Compost B effectively removed most pollutants, including Chemical Oxygen Demand (COD, Ammoniacal Nitrogen (NH3-N), were reduced by 89±4 and 96.6±0.9, respectively. The result concluded that Elaeis Guineensis leaves compost is recommended to be used as part of engineered soil media due to its capabilities in eliminating stormwater pollutants. © Published under licence by IOP Publishing Ltd.